On the anticonvulsant activity of kaurenic acid - Daló, Nelson L; Sosa-Sequera, Miriam C; Usubillaga, Alfredo (Investigación Clínica, 2009)
Kaurenic acid [(-)-kaur-16-en-19-oic acid] is a diterpene isolated from the aerial parts of Espeletia semiglobulata, one of 85 species of Espeletiinae found in Venezuela. Its anticonvulsive activity was studied using two different models of experimental seizures: spinal seizures induced by sudden cooling (SSSC) in amphibians and seizures induced by pentylenetetrazol (PTZ) in mice. In SSSC, kaurenic acid (KA) inhibited the tonic hind-limb extension with an ED50 of 2.5 mg/kg. It was 4-fold more potent than known anticonvulsant drugs such as carbamazepine and phenytoin and 100-fold more potent than valproic acid. However, KA as well as valproic acid were ineffective against the clonic phase of SSSC. In the PTZ-induced seizures, KA at doses of 0.625 and 1.25 mg/kg increased the latency of seizure onset and protected against generalized clonic-tonic seizures by 45% and 65%, respectively. The sedative effects of KA had an ED50 of 8.5 mg/kg in mice and 75 mg/kg in amphibians. This work provides experimental evidence supporting the potential value of kaurenic acid as an anticonvulsive drug.